MICROSTRUCTURAL ANALYSIS OF THE INTERFACE BETWEEN SOME SUPERALLOYS AND COMPOSITE/CERAMIC MATERIALS - BURDE, Alexandru-Victor; CUC, Stanca; RADU, Adrian; RUSU, Mircea Aurelian; COSMA, Cosmin Sorin; CÂMPIAN, Radu Septimiu; LEORDEAN, Dan (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The clinical success of aesthetic ceramic fused to metal or composite resin bonded to metal restorations depends on the quality and strength of composite/ceramic bonding. To investigate the ceramic and composite surface adhesion to the surface of the alloys, samples were prepared by using the metallographic techniques and then were analyzed by Scanning Electron Microscopy (SEM). We studied a total of four samples of superalloys, denoted S1, S2, S3, and S4. Each of these was treated with: Vita ceramic powders, Noritake ceramic powders, Premise Indirect composite and an indigenous composite C1. At a magnification level of x1500, the adherence between the layers and the surface irregularities of the layers that improve the adherence could be properly observed. It is worth noting that after the sample preparation procedure, samples S1, S2 and S4 were damaged, the only sample remaining in a good condition was sample S3.